2020
DOI: 10.1590/0100-3984.2019.0057
|View full text |Cite
|
Sign up to set email alerts
|

Background parenchymal enhancement: behavior during neoadjuvant chemotherapy for breast cancer and relationship with a pathological complete response

Abstract: Objective: To evaluate background parenchymal enhancement (BPE) and its characteristics, as well as its behavior before and after neoadjuvant chemotherapy (NAC), in both breasts of patients with unilateral breast cancer. Materials and Methods: This was a retrospective, cross-sectional observational study involving a consecutive sample of women with invasive breast cancer who underwent breast magnetic resonance imaging (MRI) between July 2007 and July 2017, as well as undergoing dynamic contrast-enhanced MRI b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
(33 reference statements)
2
3
0
2
Order By: Relevance
“…The relatively low sample size in the various categories represents our study limitation, even though it is in line with other published works [ 26 , 42 ]…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The relatively low sample size in the various categories represents our study limitation, even though it is in line with other published works [ 26 , 42 ]…”
Section: Discussionsupporting
confidence: 84%
“…The relatively low sample size in the various categories represents our study limitation, even though it is in line with other published works [26,42] A second limit may be the retrospective nature of the study. From having analyzed only two MRI steps in a significant proportion of the sample, this limit could eventually be considered apparent since the most significant changes in BPE occurred in the first treatment phase, as reported in the literature [22][23][24]30].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In recent years, it has also been suggested to use background parenchymal enhancement (BPE) in the assessment of responses to NAC, which describes the enhancement of the normal breast tissue related to physiological vascularization. La Forgia et al, indicated that BPE is an important aspect that conditions the diagnosis and that it is a potential predictive factor in the response to neoadjuvant cancer therapies in graphic contrast examinations, as already confirmed in MRI and CESM examinations [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 90%